Bladder pain syndrome. Issue 8 (August 2021) - Derbyshire, Laura; Pearce, Ian
Abstract: Bladder pain syndrome (BPS) is a condition of chronic bladder pain or discomfort that can significantly disrupt normal daily activities and reduce quality of life. It can be difficult to diagnose and manage because of vague symptoms, a poorly understood aetiology and few universally effective treatments. This article reviews the current literature on BPS aetiology, clinical presentation, diagnosis, and treatment options.